The effect of emotional color on creating expression as applied to painting / Nor Humaira Jaffri - Jaffri, Nor Humaira (Faculty of Education, 2014)
The purpose of this research is to uncover and gain an in-depth understanding of the effect of emotional color on creating expression as applied to painting. Specifically, this research aims to obtain information and to collect details about what actually influenced this painter in making their painting. This research done based on qualitative research in the form of a field study. The approach used in this research involves collecting and analyzing study data qualitatively for the most of data. The outcome of this research is based on the qualitative data collected from the interview, observations and documented evidences. This study aims is to produce an artwork and also study about the relationship between color and expression. Color and expression is important to determine how artwork will be created. There were several expression might related to color preferences that influenced painting. The researcher’s upmost aspiration from this research is to improve quality of the painting for teachers, students and future researcher.